Artificial intelligence in English writing: Ethical integration and educators’ perspectives - Ratna Yunita; Nurma Fitrianna; Nashrul Ingqidam Maulana (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
The rapid integration of AI-assisted writing tools in English language education has transformed instructional practices while raising unresolved ethical concerns related to academic integrity, student autonomy, and fairness. The research aims to explore lecturers' views regarding the application of AI in writing courses, especially concerning academic integrity, student autonomy, and fairness. Collecting data from 30 English lecturers of Islamic higher educations in Indonesia, this study examines the ethical implications of the AI-assisted writing tools’ integration in English language instruction. Using a qualitative approach, data were collected through open-ended questionnaires and analyzed thematically using NVivo software. Descriptive statistics such as percentages were used to support the presentation of qualitative themes. The results suggest that numerous lecturers recognize the advances of AI tools such as real-time feedback, improved writing accuracy, and increased efficiency concerns persist about excessive dependence on AI, erosion of critical thinking skills, and algorithmic bias. The study also reveals a lack of institutional guidelines to support ethical AI integration. The study recommends the need for a transformative approach to AI integration that moves beyond technical adoption toward ethically informed pedagogy, institutional policy reform, and the cultivation of lecturers’ and students’ critical AI literacy in higher education writing contexts.